To online or not? - Mohd Zani, Amirudin; Setia, Roszainora (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2021)
On 30th January 2020, the World Health Organization (WHO) announced COVID-19 as a public health emergency of international concern and later it was declared as global pandemic on 11th March 2020 (Cucinotta & Vanelli, 2020). Prior to that, Malaysia, revealed its first detected case of Covid-19 on 25th January 2020, traced to a Chinese tourist. On 4th of February 2020, Malaysia confirmed its first local Covid-19 case, a 41-year-old citizen (Elengoe, 2020). On the 16th of March 2020, the number of positive COVID-19 cases had reached 553, and the then Malaysian Prime Minister Tan Sri Muhyiddin Yassin announced the first Movement Control Order (MCO) from 18th March to 31st March 2020 to